HUBUNGAN DISIPLIN DAN KOMPENSASI DENGAN KINERJA PERAWAT UNIT PELAYANAN KHUSUS DI RUMAH SAKIT UMUM DAERAH KOTA LANGSA TAHUN 2017 - Hulwani, Thahrina Zatil; Ketaren, Otniel; Sembiring, Evarina; Zulfendri, Zulfendri; Manurung, Kesaktian (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Nurse performance is a determining factor in the image and quality of the hospital. Achieving maximum performance from a nurse can be seen from various factors,including discipline, employee satisfaction,which includes several aspects, namely salary increase, compensation, incentives, promotion, and so on. This research uses analytic survey with cross sectional design, which aims to analyze the relationship of discipline and compensation with the performance of special service unit nurses in Langsa City Regional Public Hospital. The population in this study were all special service unit nurses in Langsa City Regional Public Hospital in the Central Surgery (Room OK), IGD, Radiology, ICU, ICCU, NICU, PICU and Hemodialysis totaling 55 nurses. All of them are made into samples or called total sampling. The data used in this study are primary data obtained by questionnaires by respondents (nurses) and analyzed using the chi square test and multiple correlation test. Where it says there is a relationship if the value of p <0.05. Based on the results of the study, it was found that there was a relationship between discipline and the performance of special service unit nurses in Langsa City Regional Public Hospital in 2017 with a value of p = 0,000 (p <0.05); there is a relationship between compensation and the performance of special service unit nurses in Langsa City Regional Public Hospital in 2017 with a value of p = 0.005 (p <0.05); and there is a relationship of discipline and compensation with the performance of special service unit nurses in Langsa City Regional Public Hospital in 2017 with a value of p = 0,000 (p <0.05). The conclusion of this study is that there is a significant relationship between discipline and compensation with the performance of special service unit nurses in Langsa City General Public Hospital in 2017.